Associations Between Elevated Growth Differentiation Factor-15 and Sarcopenia Among Community-dwelling Older Adults. Issue 4 (13th July 2021) - Kim, Miji; Walston, Jeremy D; Won, Chang Won
Abstract: Background: Growth differentiation factor 15 (GDF-15) is associated with disease progression, mitochondrial dysfunction, and mortality. Elevated GDF-15 level was recently reported to be associated with poorer physical performance in healthy adults. However, the association between serum GDF-15 level and sarcopenia in community-dwelling older adults has not been well characterized. Methods: We conducted cross-sectional ( n = 929) and 2-year prospective analyses ( n = 788) among participants aged 70–84 years enrolled in the Korean Frailty and Aging Cohort Study. Participants with an estimated glomerular filtration rate of <60 mL/min/1.73 m 2 were excluded. Appendicular lean mass was measured using dual-energy x-ray absorptiometry. Sarcopenia status was determined according to the Asian Working Group for Sarcopenia-2019 algorithm. Results: At baseline, 16.6% of the participants had sarcopenia. Median GDF-15 concentration was higher in the sarcopenic group than in the non-sarcopenic group (1221 pg/mL vs 1019 pg/mL, p < .001). In the multivariate analysis adjusted for cardiometabolic risk and biological factors, the highest GDF-15 tertile (≥1245 pg/mL) had an increased likelihood of sarcopenia (odds ratio, 1.96; 95% confidence interval, 1.16–3.33) than the lowest tertile (<885 pg/mL). During the 2-year follow-up period, 67 (10.1%) individuals without sarcopenia at baseline developed sarcopenia. There were no significant associations between baseline serum GDF-15 levels and incident sarcopenia or its components (all p > .05). Conclusions: Elevated GDF-15 was associated with prevalent sarcopenia but not able to predict incident sarcopenia in the 2-year follow-up. Further studies are needed to explore the pathophysiological roles of GDF-15 in the development of sarcopenia.